The Geography of Innovativeness - New product announcements in The Netherlands - van der Gerben Panne; Wilfred Dolfsma (European Regional Science Association (ERSA), 2003)
In contrast to findings in other countries, and surprisingly in view of the literature, innovation in the Netherlands is not spread geographically according either to relevant labour market characteristics or to localized agglomeration economies. Instead, statistical analysis shows that the Netherlands is an urban field, and that the regional knowledge infrastructure - universities of technology in particular - is the only variable that can offer an explanation of innovative activity throughout the country. By analysing similar relationships for younger firms, we are able to make a quite strong case about causation. We estimate these regional spillovers using the Literature Based Innovation Output indicator by screening two successive volumes of 43 specialist trade journals for product announcements. Output indicators for innovativeness - except for patents, which have well-known disadvantages as an indicator - are not often used in the relevant literature, partly because they are not readily available. Our analysis offers the possibility to assess how consistent the use of input versus output indicators of innovativeness is in the analysis of the geographical spread of innovative activity.
Keywords: 330